Social economy as an alternative for socioeconomic development in Mexico - Lozano Montero, Eva (2019)
The social economy is a result of the needs of equity, employment and affordable financing to both workers and organizations, mainly micro, small and medium-sizeenterprises (MSMEs). This referenced theoretical and transversal study analyzes the impact of the social economy and its different strategies. In adittion, the study showstheir influence in the global socioeconomic development, as well as its contribution enhancing a sustainable transformation; however, it is necessary to comply with legalaspects, transparency, unification of concepts and leadership that helps to consolidate the social economy system. Thus, in this study, collective mutual funds are proposedas a supporting alternative for the enterprise socioeconomic development and competitiveness.